NDERES PROFIT SHARING MODEL ON THE BROWN SUGAR FARMERS IN NGLEGOK DISTRICT BLITAR REGENCY - Diana Elvianita Martanti; Hery Suprayitno (JARES (Journal of Academic Research and Sciences), 2019)
Profit sharing is a mutually beneficial collaboration between two or more people on mutual agreement. The purpose of this study is to find out the profit sharing model “nderes” for brown sugar farmers in Nglegok Kabupaten Blitar sub-district. One area in Blitar regency which is a producer of brown sugar is Nglegok Subdistrict. This is because Nglegok village has fertile land and there are still many coconut trees that grow up. Therefore, many Ngelgok subdistrict residents who utilize the results of coconut tree sap to be made into brown sugar even though to take coconut palm juice the risk is quite large because it is not impossible to have an accident when taking the sap, such as falling from coconut trees and others. Because of the large risk, many owners of coconut trees do not dare to climb by themselves, so in order to obtain additional income they work together with other people who dare to take the sap water with a profit sharing system. This research method used a qualitative approach with the interview method to the beneficiary, coconut tree owners and “legen” cookers in Nglegok sub-district Blitar Regency. The results of this study produce various concepts of cooperation, namely based on the results of “nderes” in the form of ounces and profit sharing based on the day.